Rights of Children with Disabilities in Slovene Law in the Light of Contemporary International Law on Children’s Rights - Murgel, Jasna (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges, 2025)
The children with disabilities are among the most marginalized people in every society, and they face various barriers that limit their ability to function, participate and enjoy their rights on an equal basis with other children. These barriers include physical, communicational, attitudinal, and environmental obstacles that are rooted in stigma and discrimination. The Convention on the Rights of the Child and the Convention on the Rights of Persons with Disabilities are the most important international treaties protecting the human rights of all children, including those with disabilities. European legal instruments, such as the European Social Charter (revised), the European Convention on Human Rights and the Charter of Fundamental Rights of the European Union protect certain rights of persons with disabilities, including children with disabilities or at least may be interpreted in a way that they protect some of their rights. Specific rights of children with disabilities are regulated by national legislation. Slovenia has implemented some of the principles of the principal international instruments regarding children with disabilities. However, in many fields, a significant improvement would be necessary to achieve genuine implementation of international legal obligations binding Slovenia in this field.